Variations in health behaviors among pregnant women during the COVID-19 pandemic - Whitaker, Kara M.; Hung, Peiyin; Alberg, Anthony J.; Hair, Nicole L.; Liu, Jihong (Midwifery, 2021)
To examine changes in lifestyle behaviors early in the COVID-19 pandemic among pregnant women. A cross-sectional internet-based survey was completed by 706 pregnant women (mean age 29.6 years ± 3.2) residing in the United States in May 2020 to assess self-reported changes in diet, physical activity, and sleep during the COVID-19 pandemic. Logistic regression analyses examined whether sociodemographic, clinical, and pandemic-related characteristics were associated with health behavior changes. Approximately 17% of women reported their diets worsened during the COVID-19 pandemic, 42% reported improvements, and 41% reported no change. For physical activity, 22% reported they stopped being active, 2% reported they became active, and 76% reported no change. Nearly one-third of participants reported getting less sleep. The factors consistently associated with adverse lifestyle changes (worse diet, stopped being active, and reduced sleep) were experiences of pregnancy complications, loss of income due to COVID-19, and changes in social connections due to COVID-19. A substantial proportion of pregnant women reported adverse lifestyle changes during the COVID-19 pandemic. Interventions during the pandemic to optimize health behaviors in pregnant women, especially among those with pregnancy complications, should address economic disadvantages and social support.